Analysis of the Current Situation of the Transition to the IPv6 Protocol in Public Entities in Peru - Cala Caso, Giovani Ruben (2025)
Currently, electronic devices (Computers, mobile devices, Routers, Servers, IoT devices, etc.) have been linked to the internet. These devices are identified by the IP address associated with each of them. Through this IP these devices have the possibility of having a connection between different networks. But in the vast majority IPv4 is usually used due to the standardization of this protocol since its beginnings on the Internet, this led to us having an exhaustion in the IPv4 address space given that there is a limited number of approximately 4.3 billion addresses, Therefore, migration from IPv4 to IPv6 is almost mandatory. However, the implementation of IPv6 in Peru is far from being achieved in the short term. In this research, an analysis will be made of the situation in which the transition to the IPv6 protocol is found in public entities in Peru, with respect to Supreme Decree No. 081-2017-PCM published on August 9, 2017.